DIÁLOGOS INTERCULTURAIS NA LITERATURA INDÍGENA CONTEMPORÂNEA: UMA PERSPECTIVA BAKHTINIANA - Brandes, Silvely (2017)
In the past years, especially after the approval of the law 11.645/08 which made obligatory the discussions about African, indigenous and afro Brazilian culture and history in the schools throughout the country, the literature written by indigenous people in Portuguese, is gaining space on the shelves of libraries and bookstores around the country. Due to the unfamiliarity with this literature, to the prejudices related to indigenous productions and even the lack of resources and support from the book publishers to the indigenous writers, a broader acknowledgment of indigenous literature is not seen in academic discussions, and little has been worked in schools about this literature. Therefore, this master`s degree dissertation is, from the language studies of the Bakhtin circle, and the discussions about hybridity and interculturality, brought by Garcia Canclini (2015) and Janzen (2005), to reflect on this indigenous literature written in the Portuguese language as a literature which is fruit of intercultural dialogues and which reveals and promotes intercultural dialogues, considering that in the works of indigenous literature the relationships between indigenous and non-indigenous, between the modern and the traditional, are present. For such, are analyzed the dialogical relations, the presence of other enunciations, in the works O Saci Verdadeiro (2000) and Ajuda do saci (2006), from Olivio Jekupé, Metade cara, Metade Máscara (2004) from Eliane Potiguara, Sehaypóry, o livro sagrado do povo Saterê-Mawé (2007) from Yaguarê Yamã, and Todas as vezes que dissemos adeus (1994) from Kaka Werá Jecupé. These works are considered as practices of social literacy, as links in the chain of verbal communication. In conclusion, I was able to realize that indigenous literature is in relationship with other indigenous and non-indigenous enunciations and that in the literature, these enunciations are being responded and anticipated. I believe this view to the intercultural dialogues in the indigenous literature contributes to the teacher who intends to work indigenous history and culture looking to these intercultural relations starting from the contemporaneous indigenous voices. May also contribute so this literature gains more space in academic discussions.